1987
DOI: 10.1016/0014-5793(87)80439-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic cluster analysis: An efficient new way to compare and analyse amino acid sequences

Abstract: A new method for comparing and aligning protein sequences is described. This method, hydrophobic cluster analysis (HCA), relies upon a two-dimensional (2D) representation of the sequences. Hydrophobic clusters are determined in this 2D pattern and then used for the sequence comparisons. The method does not require powerful computer resources and can deal with distantly related proteins, even if no 3D data are available. This is illustrated in the present report by a comparison of human haemoglobin with leghaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
461
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(468 citation statements)
references
References 22 publications
5
461
0
2
Order By: Relevance
“…Hydrophobic and polarity gradients within the loops were measured as described by Kyte and Doolittle [18] and of Grantham [19], respectively. Hydrophobic cluster analysis [20] on the amino acid sequence of the first external loop (M1-M2) was carried out using the internet site bioserv.rpbs.jussieu.fr. The modeling software used in this study are either programed for single letter or three letter amino acid codes.…”
Section: Peptide Topology Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophobic and polarity gradients within the loops were measured as described by Kyte and Doolittle [18] and of Grantham [19], respectively. Hydrophobic cluster analysis [20] on the amino acid sequence of the first external loop (M1-M2) was carried out using the internet site bioserv.rpbs.jussieu.fr. The modeling software used in this study are either programed for single letter or three letter amino acid codes.…”
Section: Peptide Topology Analysismentioning
confidence: 99%
“…After 5 turns, residues I 109 and P 126 have similar positions parallel to the axis of the cylinder. Gaboriaud et al [20] have shown that if the cylinder is cut parallel to its axis and unrolled, sets of adjacent hydrophobic residues can be encircled and termed hydrophobic clusters (see Figure 6). As some adjacent amino acids (e.g.…”
Section: Hydrophobicity and Polarity Gradients Within The First Extermentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic cluster analysis (HCA) [23] was performed to predict the structural features of IPI-O along the deduced amino acid sequence. HCA plots were generated using the program HCA-Plot2 (Doriane, Paris).…”
Section: Amino Acid Sequencing Of Recombinant Ipi-o Protein and Hydromentioning
confidence: 99%
“…The new encoding scheme can be derived in the 3-, 2-, or 1-dimensional form [19]. Finally, hydrophobic cluster analysis (HCA) analysis constitutes another well-known technique for the 2D representation of protein sequences [20][21][22][23]. Randić et al ultimately approached protein representations by using 2D schemes based on nucleotide triplet codons or virtual genetic code [24,25].…”
Section: Introductionmentioning
confidence: 99%